Influence of interlayer dwell time on the microstructure of Inconel 718 Laser Cladded components. (August 2020) - Guévenoux, Camille; Hallais, Simon; Charles, Alexandre; Charkaluk, Eric; Constantinescu, Andrei
Graphical abstract: Highlights: Characterization of Inconel 718 Laser Cladded microstructures by EBSD analyses. Impact of an interlayer dwell time on grains morphology and orientation. Cooling mechanisms highlighted: convection (surface) and conduction (kernel). Simplified thermal analysis based on melt pool shapes and solidification maps. Abstract: Laser Cladding is one of the leading additive manufacturing technologies enabling the repair of metallic components. Their fatigue reliability depends directly on the material microstructure and consequently on the process parameters. This study highlights the influence of the interlayer dwell time on single-track walls for Inconel 718 repaired components. EBSD analyses show that dwell time both reduces grain size and creates a textural stretch of the microstructure. An optimal dwell time between the writing of successive layers can then be introduced to target a specified microstructure gradient at the interface between the original part and the repaired deposit.